Training teachers to teach PISA-like reading: A case in Indonesia - Emi Emilia; Eva Tuckyta Sari Sujatna; Nia Kurniasih (Indonesian Journal of Applied Linguistics, 2022)
This paper presents partial results of the first year of a multi-year joint study, involving three universities in Indonesia, aiming to develop a program to train English and Indonesian teachers to teach PISA-like reading (24 teachers in junior and senior high schools in West Java, Indonesia). The study aimed to identify whether the program can help the teachers enhance their PISA-like reading ability, create PISA-like reading materials for reading practices, and teach them to their students. The program drew on principles of effective teacher professional development (Ajani, 2018; Borko, 2004; Borko et al., 2010; Darling-Hammond et al., 2017), PISA reading (OECD, 2009, 2016, 2017, 2019, 2021), text-based instruction (Macken-Horarik et al., 2017), Reading to Learn Program (Rose, 2020a,b), and online teaching (Ragan, 2015). The study uses a program evaluation with the data collected from four sources, including a phase of training, pre- and post-tests, collection of PISA-like reading materials, and questionnaires distributed before and after the training program. The focus of the first year was on enhancement of teachers’ understanding and skills in different PISA-related aspects. Enhancement of their teaching capacity has not been explored, except for that prior to the training program, and this has been reported in Rahmadina and Emilia (2022). The first-year results reveal that the training program could help enhance the teachers’ ability to read, to use appropriate texts, and to construct PISA-like reading tasks. This was confirmed by the teachers’ positive responses to the program, in accordance with previous research on effective teacher professional development (TPD). It is recommended that the training program be conducted in different contexts, involving more teachers to help students learn to read and succeed in PISA reading.